The Berenstain bears get stage fright - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1986)
Sister Bear worries about her lines in the school play while Brother Bear has no fear. Guess who forgets the lines during the performance?